Build and program your own LEGO Mindstorms EV3 robots - Karch, Marziah (Que, 2015)
"Step-by-step, full-color tutorial teaches modern robotics to those with minimal experience."
Obsahuje rejstřík
Keywords: roboty; programování; Lego Mindstorms EV3; robots; programming; příručky; handbooks and manuals